1998
DOI: 10.1142/s021797929800051x
|View full text |Cite
|
Sign up to set email alerts
|

Logistic Map as a Random Number Generator

Abstract: For the largest value of the control parameter, the logistic map is able to generate an infinite chaotic sequence of numbers. Here we describe a simple method for obtaining a random number generator based on this property of the logistic map. Comparing to usual congruential random generators, which are periodic, the logistic random number generator is infinite, aperiodic and not correlated. An aperiodic random number generator is a valuable tool for computer simulation methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(34 citation statements)
references
References 1 publication
0
31
0
Order By: Relevance
“…There have been proposals of generators based on unimodals chaotic maps, for example in [13,14] proposed a pseudo-random bit generator by using only one logistic map, but in [15] the authors pointed out that bit streams generated through only one chaotic system are potentially insecure due to the output may leak some information about the chaotic system. In order to overcome the aforementioned vicissitude, they proposed a pseudo-random bit generator based on a couple of piecewise linear chaotic maps, which are iterated independently and the bit streams are generated by comparing the outputs of these chaotic maps.…”
Section: Introductionmentioning
confidence: 99%
“…There have been proposals of generators based on unimodals chaotic maps, for example in [13,14] proposed a pseudo-random bit generator by using only one logistic map, but in [15] the authors pointed out that bit streams generated through only one chaotic system are potentially insecure due to the output may leak some information about the chaotic system. In order to overcome the aforementioned vicissitude, they proposed a pseudo-random bit generator based on a couple of piecewise linear chaotic maps, which are iterated independently and the bit streams are generated by comparing the outputs of these chaotic maps.…”
Section: Introductionmentioning
confidence: 99%
“…Trying to make use of the chaotic nature of simple maps, many researchers have discussed the possibility of using the logistic map to generate random numbers [12][13][14][15]. One distinct feature of chaotic maps is that at least one Lyapunov exponent of the systems is positive for certain parameter regimes.…”
Section: Test Results and The Clear Correlation With Lyapunov Exponentsmentioning
confidence: 99%
“…In fact, the idea of applying chaos theory to generate random numbers has produced interesting works in recent years [9][10][11][12][13][14][15]. For instance, Collins et al [12] have applied the logit transformation to the logistic map to produce random numbers of uniform distribution.…”
Section: Introductionmentioning
confidence: 99%
“…To guarantee the secrecy of information, numerous techniques have been developed by many researchers [2][3][4]. Over the last two decades, it has been found that there exists a close relationship between cryptology and chaos [5,6]. The behavior of chaotic signals is highly unpredictable and random-like which can be used in the design of cryptographic algorithms.…”
Section: Introductionmentioning
confidence: 99%